How to measure country-level financial reporting quality?. Issue 2 (3rd October 2016) - Tang, Qingliang; Chen, Huifa; Lin, Zhijun
Abstract : Purpose: The purpose of this study is to measure the financial reporting quality of 38 main countries (regions) in the world from 2000 to 2014. Design/methodology/approach: This paper uses six accounting and auditing indicators to construct a comprehensive index for the measurement of country-level financial reporting quality. To test the validity of the methodology, the index to test institutional impacts on national financial reporting quality is used. Findings: It was found that the results are consistent with the predictions and previous studies. The evidence suggests that the quality measure in this paper is innovative and appropriate and can provide a useful tool for researchers who are concerned with financial reporting quality at the country level. Originality/value: The study is the first in the literature to use both accounting and auditing data to construct financial reporting quality indicators. The study should help international investors assess investment risks in foreign financial markets so as to make an informed decision. In addition, the diversity of financial reporting practices documented in the paper should prompt market regulators, accounting standard setters and professional accounting bodies to reinforce the efforts on international convergence of accounting and financial reporting standards and practices.